Ethnic-conflict and its manifestations in the politics of recognition in a multi-ethnic Niger delta region - Olakunle Michael Folami (Cogent Social Sciences, 2017)
Conflict over oil exploitation and exploration by the multinational oil companies has manifested in different forms in the Niger Delta such as intra and inter-ethnic conflict. Distribution of oil wealth is characterised with marginalisation, bias, nepotism and alienation in the region. Most times, lack of recognition in oil wealth distribution led to ethnic conflict. The ethnic conflict in turn has affected family relations, identity and economy; it has led to a deep division among various ethnic groups in the region like the Urhobo, The Ijaw and the Itsekiri. In this study, Recognition Theory was used to examine the epistemology of ethnic conflict in the Niger Delta. This study was carried in Delta State. Purposive method of data collection was used to select one hundred and twenty eight participants such as traders, artisans, civil society members, civil servants, farmers, traditional figures, political office holders and opinion leaders. This study found that the ethnic conflict was a fall out of oil exploration and exploitation in the Niger Delta. The ethnic conflict has a chain of reactions on identity, name, family, economy, settlement and tradition. This paper concluded that redistribution of oil wealth among the ethnic group would contribute to enduring peacebuilding in the Niger Delta region.